Europeanization and new member states : a comparative social network analysis - Jurje, Flavia. (Routledge advances in European politics ;, 2013)
"This book examines the Europeanization of the polity and politics of a new EU Member State. Using social network analysis in a comparative research design, it provides a systematic analysis of the effects of Europeanization on the institutions, policy processes, power constellation and conflict among national elites"--